2019
DOI: 10.1055/s-0039-1695799
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Delayed Cord Clamping in Infants of Diabetic Mothers

Abstract: Objective To investigate the effect of delayed cord clamping (DCC) in infants of diabetic mothers. Study Design Women who had diabetes throughout their pregnancy and gave birth at 37 weeks of gestation or later were included in the study along with their babies. Early cord clamping was performed as soon as possible after birth, while DCC was performed by clamping 60 second after birth. The two groups were compared in terms of venous hematocrit (htc) levels and rates of hypoglycemia, jaundice requirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…22 In our study, rates of hypoglycemia, hypoglycemia requiring glucose infusion, and hypocalcemia were all higher in the ECC group than in the DCC group, but there was also no statistically significant difference. Our results are approximately similar to a previous study, 13 , but they did not discuss hypocalcemia in their results.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…22 In our study, rates of hypoglycemia, hypoglycemia requiring glucose infusion, and hypocalcemia were all higher in the ECC group than in the DCC group, but there was also no statistically significant difference. Our results are approximately similar to a previous study, 13 , but they did not discuss hypocalcemia in their results.…”
Section: Discussionsupporting
confidence: 91%
“…The sample size was calculated by using power and sample size software version 3.0. Based on a previous study done by Korkut et al, 13 the percentage of neonates who needed NICU admission was 27.5% in the early clamping group compared with 10.0% in the delayed clamping group. The total sample size of 154 (77 per group) will be sufficient to detect power of 80% and a significance level of 5%.…”
Section: Sample Size Estimationmentioning
confidence: 84%
See 2 more Smart Citations
“…However, a recent study observed that DCC in NDMs was not associated with a higher rate of neonatal jaundice requiring phototherapy, although performing DCC led to an increased polycythemia ratio, which may be the result of the insufficient sample size. 16 Treatments, whether dietary modification or pharmacological therapies, have been proven to reduce immediate adverse outcomes for neonates-improving some pregnancy outcomes by reducing fetal overgrowth, maternal adiposity, and pregnancy-related hypertension-so a consensus has been reached. 6,17 There are, however, conflicting findings with regard to other outcomes, such as neonatal hyperbilirubinemia and jaundice requiring phototherapy, and neonatal hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%